IS HODGKIN’S DISEASE AN INFECTIOUS DISEASE? - N. Izadian (Iranian Journal of Public Health, 1979)
The exact cause or causes of Hodgkin's disease have not yet been determined. The etiology of the disease suggests, but has not verified, a possible immunological and/or viral relationship. The article reviews the literature on the epidemiology and etiology of Hodgkin’s disease from 1955 to the present. The author presents several clinical phenomena that are commonly associated with Hodgkin’s disease and which may be useful as diagnostic tools in cases of suspected Hodgkin's disease or with suspicious pathology. The author concludes by suggesting possible areas for future research.